2014
DOI: 10.1590/s2236-89062014000200006
|View full text |Cite
|
Sign up to set email alerts
|

Orchidaceae em um fragmento de Floresta Semidecídua de encosta na região sul do Estado do Espírito Santo, Sudeste do Brasil

Abstract: -(Orchidaceae in a fragment of semideciduous slope forest in the southern Espírito Santo State, Southeastern Brazil). The present study aimed to inventory and elaborate descriptions and illustrations for the species of Orchidaceae found in a forest located in the southern Espírito Santo State, a region of few botanical studies, featuring a poorly known flora. During the study, 25 species were found and distributed into 21 genera. The majority of the species were epiphytic, represented by 16 species, followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…as terrestrials, which is similar to the statistics reported by Dressler (1981) in which about 25% of the orchid species are exclusively terrestrials. This result is similar to that of Krahl et al (2014), who studied the semideciduous forest of South part of Espírito Santo State, finding values of 22.22% of terrestrial orchids. In this study, the authors recorded a total of 22 species; of all these, twelve were in an altitude-field vegetation, which can be related to the lower vegetative competition index for this kind of vegetation, due to the lowest occurrence of plant species.…”
Section: Resultssupporting
confidence: 91%
“…as terrestrials, which is similar to the statistics reported by Dressler (1981) in which about 25% of the orchid species are exclusively terrestrials. This result is similar to that of Krahl et al (2014), who studied the semideciduous forest of South part of Espírito Santo State, finding values of 22.22% of terrestrial orchids. In this study, the authors recorded a total of 22 species; of all these, twelve were in an altitude-field vegetation, which can be related to the lower vegetative competition index for this kind of vegetation, due to the lowest occurrence of plant species.…”
Section: Resultssupporting
confidence: 91%
“…Its establishment in various regions seems to be closely related to light availability and stomatal density since, although it is a species well adapted to disturbed or undisturbed soils, it exhibits a combination and convergence of anatomical characteristics of its different organs that allow for its adaptation to environments with high light intensities as well as to those that are humid and shady (Riverón-Giró et al, 2017). Such adaptability has been demonstrated by Rahal, Souza-Leal, and Pedroso-de-Moraes (2015), who reported the occurrence of O. maculata in areas of high light intensities in Araras, São Paulo State, Brazil, whereas, on the other hand, Krahl, Cogo, and Valsko (2014) found a well-established population of this species in a shady area of a semi-deciduous forest in the State of Espírito Santo, Brazil, blooming from January through March. In the present study flowering was also observed in this period.…”
Section: Acclimatizationmentioning
confidence: 90%
“…For species identification and description, we used the relevant literature for M. sect. Rufescens (Illg 1977;Christenson 2002;Bogarín and Pupulin 2010;Krahl et al 2014;Arévalo et al 2015;Engels and Ferneda-Rocha 2016;Marcusso et al 2018). The names of the authors and abbreviations follow Brummitt and Powell (1992).…”
Section: Methodsmentioning
confidence: 99%